2005
DOI: 10.1128/aac.49.4.1593-1596.2005
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activities of Fluconazole and Voriconazole with Terbinafine against Four Candida Species Determined by Checkerboard, Time-Kill, and Etest Methods

Abstract: The in vitro activities of fluconazole or voriconazole plus terbinafine were evaluated against 20 Candida isolates by the checkerboard, time-kill, and Etest methods. Synergism (C. albicans, C. glabrata, and C. tropicalis) and indifference (C. krusei) were observed. Correlation among methods was good. The Etest is a suitable method to determine drug interactions.The checkerboard and time-kill methods to determine in vitro interactions between drugs are time-consuming and cumbersome for use in clinical laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 18 publications
2
46
1
1
Order By: Relevance
“…On the contrary, the agreement of time-kill assay with the other 3 methods was low. In general, the agreements obtained in the literature are diverse (Bonapace et al, 2000;Cantón et al, 2005;Lewis et al, 2002;Martin, 2010;Orhan et al, 2005;White et al, 1996). However, a variety of investigators found disagreement between checkerboard and time-kill results (Cappelletty and Rybak, 1996;Chang et al, 2007;Visalli et al, 1988;White et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, the agreement of time-kill assay with the other 3 methods was low. In general, the agreements obtained in the literature are diverse (Bonapace et al, 2000;Cantón et al, 2005;Lewis et al, 2002;Martin, 2010;Orhan et al, 2005;White et al, 1996). However, a variety of investigators found disagreement between checkerboard and time-kill results (Cappelletty and Rybak, 1996;Chang et al, 2007;Visalli et al, 1988;White et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…This approach is based on some synergistic definitions applied for combinations involving 2 antimicrobials using checker-board (Mackay et al, 2000;Rand et al, 1996), Etest (Cantón et al, 2005;Lewis et al, 2002;Sopirala et al, 2010) and time-kill assay (Eliopoulos and Eliopoulos, 1988;NCCLS/CLSI, 1999). Table 1 presents the scheme proposed to classify an interaction as negative, indifferent, additive, or potentiation.…”
Section: Classification Of a Combination As Negative/indifferent/addimentioning
confidence: 99%
“…8,12 Thus, combining antifungal agents has been suggested as an alternative strategy, and the use of terbinafine in combination with azoles has been suggested as a potential therapeutic option. [4][5][6]13 Despite promising results obtained through some antifungal associations against Candida spp., only the combination of caspofungin with terbinafine has already been tested against C. dubliniensis. 14 Differential effects were detected when C. albicans and C. dubliniensis were exposed to the same antifungal combination; it is acceptable the evidence of negative effects against C. dubliniensis.…”
Section: Brief Communicationmentioning
confidence: 99%
“…While the combination of azoles with amphotericin B has provided controversial results, 3 most of studies have found additive or synergistic effect when azoles were combined with terbinafine against C. albicans. [4][5][6] Other Candida spp. have also been evaluated, 5 but little is known about the effects of antifungal combinations against Candida dubliniensis.…”
mentioning
confidence: 99%
See 1 more Smart Citation